GORKY AND “THE GOSPEL OF THE NEW FAITH” (Филологический класс, 2018)
M. Gorky’s position towards defining the socialist realism is complex and in order to understand it correctly one must analyse his intellectual, political and literary evolution as a whole. Gorky felt “the need to enrich both the economical and socio-political aspects of Marxism with morally-ethical and philosophically-religious meaning” and was exhilarated by his deep belief in man. His understanding of Marxism happened via his perception of Nietzsche and therefore his views were based on romantic, Nietzschean worldview. During his visit to the United States Gorky for the first time defined socialism as the future religion of humanity that will free the world of poverty and the reign of wealth. Gorky would remain faithful to these ideas his whole life. It was no accident that Gorky chose his article “The disintegration of Personality” printed in 1909 in the “Essays on the Philosophy of Collectivism” collection, which was refused by Lenin for including the dangerous ideas of Bogdanov and later in 1934 fully accepted by Stalin, for his speech at the First Soviet Writers’ Congress. Here the religion of humanity, redeemed by the mysticism of labor, emerges again. This idea captivated him during his friendship with Lunacharsky. In order to fit in the new Party ideology Gorky didn’t have to reorganize himself. He sees no anarchistic threat in the peasantry controlled by Stalin’s policy, like in 1917, but rather a possibility of long-awaited difficult cultural redemption. The idea of socialist industrialization of Russia was more appealing to Gorky than Lenin’s idea of the revolution. Socialist realism, as writes Cesare De Michelis has many points in common with the Russian religious tradition. In this context, the Gorky’s speech on the first Soviet Writers’ Congress, which «instead of complying with Lenin’s ideology was based on “heresy”, heavily criticized by Lenin before, “the God Building”, was a reflection of traditional Russian religiousness that Joseph Vissarionovich (Stalin), former trainee priest, understood perfectly. During the First Soviet Writers’ Congress it became obvious that the idea of “God-building”, developed in the novel “Confession”, was reborn in Gorky’s speech, although in a clouded but still recognizable way. The publicist success of the speech led to its incorrect understanding. Speaking about Gorky as “the founder of socialist realism” without referencing to the evolution of his literary and artistic position would be an unforgivable simplification that can distort the real picture.